Parametric analysis to optimize a tradeoff between the efficiency and demagnetization of line-start permanent magnet synchronous motors - Tuan, Le Anh; Thuy, Trinh Bien; Y., Do Nhu (Institute of Advanced Engineering and Science, 2026)
The line-start permanent magnet synchronous motors (LSPMSMs) have many advantages, such as high efficiency and power factor, high energy density, and the ability to line-start. Therefore, the LSPMSMs are being studied to partially replace the induction motors (IMs) currently in use. However, LSPMSMs have disadvantages, including poor starting capability, and the permanent magnets may experience irreversible demagnetization during operation. Thus, this paper uses parametric analysis method to analyze the size of the permanent magnets to optimize the efficiency of the motor while ensuring that the permanent magnets do not undergo irreversible demagnetization. A 15 kW, 2-pole LSPMSM was used for experimentation, and the results show that the motor achieves the highest efficiency of ηmax = 95.5% at wM = 35 mm. However, when the motor thickness wM is greater than or equal to 34 mm, the motor experiences significant demagnetization. Thus, selecting permanent magnets (PM) size and material type that balance motor efficiency and avoid irreversible demagnetization needs careful consideration. Additionally, the experimental and simulation results are consistent, confirming the accuracy between the two methods.